Characterization of Glasses in One Type of Alumina Rich Fly Ash by Chemical Digestion Methods: Implications for Alumina Extraction - Lijun Zhao; Hanshuang Xiao; Baodong Wang; Qi Sun (Journal of Chemistry)
In recent years, one type of alumina rich fly ash (ARFA) with about 50 wt% of alumina has been extensively investigated for alumina extraction in China. Due to the silica in ARFA, alumina extraction would have to generate a huge amount of solid waste. There is a growing interest in the glasses in ARFA, because they are composed mainly of silica and could be removed prior to alumina extraction. In this work, the glasses in ARFA have been investigated by chemical methods, that is, acid and base digestions. The chemical compositions have been measured by XRF for ARFA from the digestion processes. The K2O standard, XRD, and FTIR spectroscopies were successfully used to define the digestions processes, and size analysis and SEM-EDX provided rich information on particle transformations. As a result, acid and base digestion methods were found to produce very similar results for the glasses in ARFA. The K2O standard was attributed to the formation of glasses by illites, and TiO2 and Fe2O3 were proposed to originate from ilmenite in alumina rich coals (ARC). Some implications of the results were also discussed for the alumina extraction from ARFA.